Экстра- и интраорганные артерии мышц голени собаки - Гончарь, М.Г. (Вестник зоологии, 1975)
The topography and intraorganic distribution of arteries in the tibia muscles were studied in 10 dogs (o and 9) by the method of postmortal angioroentgenography and preparation. It is established that most tibia muscles get nutrition from the arteries the number of which varies from 1 to 12. The gastrocnemius muscle, interior tibia muscle, extensor digitorum longus and flexor digitorum profundus possess the greatest number of vessels. The ramification of intramuscular arteries is chiefly of scattered or main line character